Best Executive in Securities Markets: An Application of Signaling and Agency Theory: Discussion - Smidt, S. (Journal of Finance, 1982)
S. Smidt, Best Executive in Securities Markets: An Application of Signaling and Agency Theory: Discussion, The Journal of Finance, Vol. 37, No. 2, Papers and Proceedings of the Fortieth Annual Meeting of the American Finance Association, Washington, D.C., December 28-30, 1981 (May, 1982), pp. 519-521